Trade Integration as a Way Forward for the Arab World : A Regional Agenda - Chauffour, Jean-Pierre (2012)
The current political turmoil for more open and participative societies in many Arab countries coupled with the emergence of new growth poles around the world could create the conditions for a big push toward greater regional and global trade integration of the Arab world. Further integrating Arab countries among themselves and opening up the region to the rest of the world are two complementary avenues to improve market access, promote behind-the-border regulatory reforms, facilitate cooperation on regional public goods, foster the emergence of an "Arab factory" through regional supply chains and productions networks, and eventually create the conditions for more and better paid jobs for the growing Arab workforce. A more ambitious trade agenda in the context of the Pan-Arab Free Trade Area would be a good place to start. Although difficult and challenging, and requiring a good dosage of flexibility and variable geometry, such an agenda would consist of (1) completing the free movement of goods within the Pan-Arab Free Trade Area, notably through the elimination of unnecessary non-tariff barriers; (2) implementing a regional initiative to liberalize services trade, including identifying a number of pilot service sectors for early regional liberalization; and (3) strengthening the rules and discipline applicable to regional trade and other policies of common interest.